A tale of one city: intra-institutional variations in migrating VLE platform - James Toner; Ian Glover; Connie Tse; Leona Norris; Farzana Latif; Anna Campbell (Association for Learning Technology, 2012)
City University London committed in 2009 to make Moodle the Virtual Learning Environment (VLE) at the core of a new Strategic Learning Environment (SLE) comprised of VLE, externally facing website and related systems such as video streaming and virtual classrooms. Previously, the WebCT VLE had been separate from most of the other systems at the institution with very limited connections to other tools. Each of the schools within the institution was able to pursue their own strategy and timeframe for the migration and embedding of Moodle within their subject areas, within an absolute limit of 2 years. This paper outlines the approaches taken by the various schools, highlighting similarities and differences, and draws out common aspects from the project to make recommendations for institutions seeking to undertake similar migrations.